INTEGRASI PENDIDIKAN BERKARAKTER DALAM PEMBELAJARAN BAHASA INGGRIS - OCTAVITA, RR. ASTRI INDRIANA; SARASWATI, RIA (UNIVERSITAS PGRI MADIUN, 2017)
AbstractThis study is aimed to integrated between character education and teaching of English Language for kindergarten teachers in LPI NUR HIKMAH Kampung Sawah. The Urgent of the theme as an expression that shows to the teachers about how to the implementation of teaching the English Language based on character education. English as an International Language needs to be developed in school learning process, but conventional language learning tends to be centered on the teacher and ignore the existence of learners. Learning English is good not only in developing cognitive abilities but also instill the value of the learners. The values of character education inEnglish subjects are friendly, caring, social, curiosity, democratic, independent, hard work, discipline, and love to read. The values of character education can be embedded in learners with learning English contextually. Constructivism concepts, inquiry, and questioning, are relevant to the values of independence, hard work, and curiosity. Meanwhile, the values of friendship, social care, discipline, love to read, and democracy can be implanted with the concept of modeling reflection and authentic assessment. The values of learning English based on character education are making students construct knowledge of English actively, gain knowledge through experience, discuss in groups and working in groups. In addition, the teacher presents the model as an example of learning, makes the reflection at the end of the meeting, and makes the process of assessment. Therefore, the resulting output is the ability of teachers to implement character education in learning English so that learning English does not tend to be centered on teachers and ignore the existence of learners. The values of character education in English subject are friendly, caring, social, curiosity, democratic, independent, hard work, discipline, and love to read. Abstrak Tujuan diadakannya pengabdian masyarakat ini adalah memberikan pelatihan penerapan pendidikan berkarakter dalam pembelajaran Bahasa Inggris bagi guru TK LPI NUR HIKMAH Kampung Sawah. Bahasa Inggris sebagai Bahasa International, memang perlu dikembangkan dalam pembelajaran disekolah akan tetapi pembelajaran bahasa yang konvensional cenderung berpusat pada guru dan mengabaikan keberadaan peserta didik. Pembelajaran Bahasa Inggris yang baik tidak hanya mengembangkan kemampuan kognitif namun juga menanamkan nilai pada diri peserta didik. Nilai-nilai pendidikan karakter pada mata pelajaran Bahasa Inggris adalah bersahabat, peduli, soial, rasa ingin tahu, demokratis, mandiri, kerja keras, disiplin, dan senang membaca. Nilai-nilai pendidikan karakter dapat ditanamkan pada diri peserta didik dengan pembelajaran Bahasa Inggris secara kontekstual. Konsep contructivism, inquiry, dan questioning relevan dengan nilai-nilai mandiri, kerja keras, dan rasa ingin tahu. Sedangkan, nilai- nilai bersahabat, peduli sosial, disiplin, gemar membaca, dan demokratis dapat ditanamkan dengan konsep learning community modeling reflection dan authentic assessment. Prosedur pembelajaran Bahasa Inggris yang berkarakter adalah membuat peserta didik mengkonstruksi pengetahuan Bahasa Inggris secara aktif, memperoleh pengetahuan melalui pengalaman, berdiskusi dalam kelompok, dan bekerja dalam kelompok. Di samping itu, guru menghadirkan model sebagai contoh pembelajaran, melakukan refleksi di akhir pertemuan, dan melakukan proses penilaian. Oleh karena itu, luaran yang dihasilkan adalah kemampuan guru dalam menerapkan pendidikan berkarakter di dalam pembelajaran Bahasa Inggris sehingga pembelajaran Bahasa Inggris tidak cenderung berpusat pada guru dan mengabaikan peserta didik.Nilai-nilai pendidikan karakter pada mata pelajaran Bahasa Inggris adalah bersahabat, peduli, sosial, rasa ingin tahu, demokratis, mandiri, kerja keras, disiplin, dan senang membaca.